Concept Of Idealism Philosophy In Islamic Education According To Imam Al-Ghozali - SUHAIMI, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The philosophy of Idealism is a philosophical system that emphasizes the importance of the superiority of the thoughts (mind). A mind is a form that can realize the world, even as a catalyst and driving force of all human behavior. Throughout history, the philosophy of idealism is related to religion because they both focus on the spiritual aspect. Thus the study of the flow of philosophical idealism towards Islamic education includes issue objectives of Islamic education, Islamic education curriculum, the teaching methods of Islamic education, the learning material of Islamic education, learners’ position in Islamic education.RESUMEN La filosofía del idealismo es un sistema filosófico que enfatiza la importancia de la superioridad de los pensamientos (mente). Una mente es una forma que puede realizar el mundo, incluso como catalizador y fuerza impulsora de todo comportamiento humano. A lo largo de la historia, la filosofía del idealismo está relacionada con la religión porque ambos se centran en el aspecto espiritual. Así, el estudio del flujo del idealismo filosófico hacia la educación islámica incluye objetivos temáticos de la educación islámica, el plan de estudios de la educación islámica, los métodos de enseñanza de la educación islámica, el material de aprendizaje de la educación islámica, la posición de los estudiantes en la educación islámica.